2017
DOI: 10.1111/bjd.15716
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Eph receptor B1 and ephrin B2 in port-wine stain endothelial progenitor cells contributes to clinicopathological vasculature dilatation

Abstract: PWS ECs are differentiation-impaired, late-stage endothelial progenitor cells with a specific phenotype of CD133 /CD166 /EphB1 /EfnB2 , which form immature venule-like pathoanatomical vasculatures. The disruption of normal EC-EC interactions by coexistence of EphB1 and EfnB2 contributes to progressive dilatation of PWS vasculatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 47 publications
(56 reference statements)
7
62
0
Order By: Relevance
“…Human dermal microvascular endothelial cells (hDMVECs) were cultured in endothelial cell basal medium (ECBM) with growth supplement (Cell Applications, Inc.) as previously described. 12 In order to establish the EC models with coexpression of EphB1 receptors and ephrin-B2 ligands, which mimic the pathological phenotypes of PWS ECs, we isolated a subset of normal hDMVECs with high expression of surface EphB1 receptors via biotinylated chimera ephrin-B2-Fc, which contains the extracellular portion of ephrin-B2 ligands and is capable of binding to EphB1 receptors, and streptavidin-conjugated magnetic beads. The rationale of this selection is that the ephrin-B2-Fc chimera ligand binds to EphB1 þ ∕EphB4 þ expressing venous and capillary hDMVEC subpopulation, while the remaining arterial hDMVEC subpopulation (EphB1 − ∕EphB4 − ) express ephrin-B2 ligands.…”
Section: Human Dermal Microvascular Endothelial Cell Culture and Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…Human dermal microvascular endothelial cells (hDMVECs) were cultured in endothelial cell basal medium (ECBM) with growth supplement (Cell Applications, Inc.) as previously described. 12 In order to establish the EC models with coexpression of EphB1 receptors and ephrin-B2 ligands, which mimic the pathological phenotypes of PWS ECs, we isolated a subset of normal hDMVECs with high expression of surface EphB1 receptors via biotinylated chimera ephrin-B2-Fc, which contains the extracellular portion of ephrin-B2 ligands and is capable of binding to EphB1 receptors, and streptavidin-conjugated magnetic beads. The rationale of this selection is that the ephrin-B2-Fc chimera ligand binds to EphB1 þ ∕EphB4 þ expressing venous and capillary hDMVEC subpopulation, while the remaining arterial hDMVEC subpopulation (EphB1 − ∕EphB4 − ) express ephrin-B2 ligands.…”
Section: Human Dermal Microvascular Endothelial Cell Culture and Tranmentioning
confidence: 99%
“…11 Recently, we found that EphB1 receptors and ephrin-B2 ligands are coexpressed on the lesional endothelial cells (ECs) in patients with port wine stains (PWSs). 12 Due to their abundance on a variety of cell types, Eph receptors and their ligands have become viable targets for therapeutic agents that can be conjugated to various targeting moieties including peptides, antibodies, and the ephrins themselves. [13][14][15][16][17][18][19][20] For example, Blevins et al 15 conjugated a peptide that targets EphA2 and EphA4 to a PEG linker and a polymer for the delivery of therapeutic plasmids to the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Tan et al . the authors investigate the anatomy of PWS capillaries and expression of developmental markers on ECs in PWS tissue samples.…”
mentioning
confidence: 93%
“…The paper by Tan et al . provides new evidence supporting the hypothesis that PWS is caused by disruption during development and that this affects EC phenotype.…”
mentioning
confidence: 93%
See 1 more Smart Citation